10.4 Solving Equations in Factored Form

Slides:



Advertisements
Similar presentations
Solving Quadratic Equations by Factoring. Remember: When solving a quadratic equation by factoring, you must first start with an equation set equal to.
Advertisements

7-5 solving quadratic equations
Thinking Mathematically Solving Quadratic Equations.
CRASH COURSE IN QUADRATICS In preparation for the Algebra CST -b + b 2 – 4ac 2ac √ (x+4)(x-3)=0 (x+1)(x+2) X 2 – 5x +4 F O I L Complete The Square.
Solving Quadratic Equations using Factoring.  has the form: ax 2 + bx + c = 0 If necessary, we will need to rearrange into this form before we solve!
Using the Quadratic Formula to Solve a Quadratic Equation
6.6 Quadratic Equations We will multiply binomials using the FOIL method. We will factor trinomials We will solve quadratic equations by factoring. We.
Section 10.5 – Page 506 Objectives Use the quadratic formula to find solutions to quadratic equations. Use the quadratic formula to find the zeros of a.
What are quadratic equations, and how can we solve them? Do Now: (To turn in) What do you know about quadratic equations? Have you worked with them before?
Algebra 9.5 Solving Quadratic Equations Using the Quadratic Formula This is an important section as there are many questions on the STAR test about the.
The Quadratic Formula. What does the Quadratic Formula Do ? The Quadratic formula allows you to find the roots of a quadratic equation (if they exist)
Today in Pre-Calculus Go over homework Notes: –Quadratic Functions Homework.
Factor. 1)x² + 8x )y² – 4y – 21. Zero Product Property If two numbers multiply to zero, then either one or both numbers has to equal zero. If a.
Quiz 1) 2). Multiplying a Trinomial and Binomial We can’t FOIL because it is not 2 binomials. So we will distribute each term in the trinomial to each.
To add fractions, you need a common denominator. Remember!
Thinking Mathematically Algebra: Equations and Inequalities 6.6 Solving Quadratic Equations.
The Quadratic Formula Students will be able to solve quadratic equations by using the quadratic formula.
Solving Quadratic Equations – Quadratic Formula The following shows how to solve quadratic equations using the Quadratic Formula. A quadratic equation.
Do Now 1) Factor. 3a2 – 26a + 35.
Example 1A Solve the equation. Check your answer. (x – 7)(x + 2) = 0
WARM UP Find the product. 1.) (m – 8)(m – 9) 2.) (z + 6)(z – 10) 3.) (y + 20)(y – 20)
Solving by Substitution Method or Elimination (Addition) Method
5.3 Factoring Quadratic Function 12/7/2012. are the numbers you multiply together to get another number: 3 and 4 are factors of 12, because 3x4=12. 2.
2.1 – Linear and Quadratic Equations Linear Equations.
Slide Copyright © 2009 Pearson Education, Inc. 6.9 Continued Solving Quadratic Equations by Using Factoring and by Using the Quadratic Formula.
Solving Quadratic Equations. Factor: x² - 4x - 21 x² -21 a*c = -21 b = -4 x + = -21 = x 3x3x x 3 (GCF) x-7 (x – 7)(x + 3)
Solving Quadratic Equations. Find the quadratic equation if the solutions are 3 and -2. x = 3 x = -2 Make them equal zero. x – 3 = 0x + 2 = 0 (x – 3)(x.
5.3 Factoring Quadratic Function 11/15/2013. Multiplying Binomials: FOIL First, Outside, Inside, Last Ex. (x + 3)(x + 5) ( x + 3)( x + 5) (x + 3)(x +
10.6 solving quadratic equations by factoring Solve x 2 + 2x – 3 using the quadratic formula X = 1 & -3 Now, factor the same equation (x + 3)(x – 1) Set.
Objective: Use factoring to solve quadratic equations. Standard(s) being met: 2.8 Algebra and Functions.
2.2 Solving Quadratic Equations Algebraically Quadratic Equation: Equation written in the form ax 2 + bx + c = 0 ( where a ≠ 0). Zero Product Property:
Skill Check Factor each polynomial completely.. 5-1: Solving Quadratic Equations by Factoring By Mr. Smith.
Aim: What are the properties of a quadratic equation?
Solve equations by factoring.
The Quadratic Formula..
Solving Equations by Factoring
Solve a quadratic equation
Solving Quadratics By Factoring (a≠1)
Tuesday You need: - Calculator - Whiteboard, marker, eraser.
Factoring Quadratic Expression
What You Will Learn Solving Quadratic Equations by Using Factoring
3-2: Solving Linear Systems
A quadratic equation is written in the Standard Form,
Algebra: Equations and Inequalities
Algebra 1 Section 12.5.
5.6 – The Quadratic Formula And Ch 5 Review
The Quadratic Formula.
9-6 The Quadratic Formula and Discriminant
Algebra 1     Define the absolute value equation however you would like with your class. Copyright © 2011 Pearson Education, Inc.
Solving Quadratics by Factoring
Warm Up ~ Unit 2 Day 1 Given x2 + 5x + 6 =0… Factor:
Algebra 12.4 Completing the Square.
Solving Quadratic Equations by Factoring
Review: Simplify.
3-2: Solving Linear Systems
Standard Form Quadratic Equation
Solving Quadratic Equations
Rational Equations.
How do we solve quadratic inequalities?
3-2: Solving Linear Systems
Homework Lesson 5.3_page 296 # ALL.
Warm-up  .
Intro to Quadratic Equations.
The Quadratic Formula..
Warm Up ~ Unit 2 Day 1 Solve by factoring: 3
3-2: Solving Linear Systems
Solving Equations by Factoring
Skills Check Factoring (after the HW Check)
Section 9.1 “Properties of Radicals”
Presentation transcript:

10.4 Solving Equations in Factored Form Algebra 10.4 Solving Equations in Factored Form

Quadratic Equations in Standard Form You have already learned the standard form of a quadratic equation: ax² + bx + c = 0 where a ≠ 0

Quadratic Equations in Factored Form Consider the equation: x² + 8x + 15 = 0 Here is the same equation, in factored form: (x + 5)(x + 3) = 0 FOIL to be sure x² +3x +5x +15 x² + 8x + 15 = 0

Two Ways to Solve: x² + 8x + 15 = 0 Quadratic Formula Factored form (x + 5)(x + 3) = 0 -8 ± 8² - 4(1)(15) √ x = 2(1) This means that for the equation to be true, either: -8 ± √ 4 x = or x + 5 = 0 x + 3 = 0 2 -5 -5 -3 -3 -8 ± 2 -6 -10 x = = x = -5 x = -3 2 2 2 x = -3, -5 x = -3, -5

ZERO PRODUCT PROPERTY If a product equals zero, then one of the factors must be 0. If ab = 0, then either a = 0 b = 0 or both = 0

Apply the ZERO PRODUCT PROPERTY…… We said that the solutions to the equation x² + 8x + 15 = 0 or (x +5)(x + 3) are -3 and -5. Substitute each solution into the equation in factored form: (-3 + 5)(-3 + 3) = 0 Substitute -3 for x (2) (0) = 0 TRUE (-5 + 5)(-5 + 3) = 0 Substitute -5 for x (0) (-2) = 0 TRUE Substitute into original equation: (-3)² + 8(-3) + 15 = 0 True (-5)² + 8(-5) + 15 = 0 True

Try these (x + 7) (x – 3) = 0 x = -7 or x = 3 (x - 4)(x – 5) = 0 +5 +5 +3 +3 2x = 5 x = 3 2 2 5 x = x = 3 2

Shortcut: (x + 7) (x – 3) = 0 -7 +3 When the factors are in the form (x +__ ) or (x - __ ) the solutions will always be the opposite of the factors, in this case -7 and +3. (x + 7) (x – 3) = 0 Ask yourself: what value of x will make this binomial = 0? Ask yourself: what value of x will make this binomial = 0? -7 +3

Shortcut: (3 + 2) (3x + 2) (x – 1) = 0 The other solution is +1 -2 = 0 Ask yourself: what value of x will make this binomial = 0? The other solution is +1 -2 (3 + 2) = 0 3 The denominator would cancel with 3 when multiplied The numerator would cancel with +2 when added 2 One solution is - 3

Try these x = -½ or x = 3 (2x + 1) (x – 3) = 0 (3x - 4)(2x + 5) = 0

A Few together from the HW P. 600 #29, 43

Homework pg. 600 # 19 - 46, 69-77